Avaliação da atividade leishmanicida de espécies reativas do oxigênio para Leishmania Leishmania chagasi - Carvalho, Sueli Silva de (2013)
Leishmaniasis are infectious diseases caused by protozoa of the genus Leishmania, that are digenetic parasites alternating between an extracellular promastigote stage (in sand fly vector) and an intracellular amastigote stage (in mammalian host). Promastigote phagocytosis results in a macrophage respiratory burst in vitro, leading to the generation of reactive oxygen species (ROS) such as superoxide anion (O2 -), hydrogen peroxide (H2O2), singlete oxygen (1O2) and hydroxyl radical (OH). Thus, we aimed to evaluate in vitro ROS toxicity for L. L. chagasi promastigotes, as well as for their amastigote counterparts. To evaluate ROS toxicity for promastigotes, we selected 16 L. L. chagasi isolates (in log phase growth) and incubated them under increasing concentrations of menadione (0-750ìM) for 4 hours, after which we determined ROS viability for these parasites by quantifying the number of mobile forms. For ROS toxicity for amastigote L. L. chagasi, we infected J774.16, a murine macrophage cell line, with ROS susceptible and resistant L. L. chagasi (in stationary phase of growth) in cultures treated by LMNA, an iNOS inhibitor (to block the synthesis of nitric oxide), treatment with diethyldithiocarbamate (DETC), a SOD-1 inhibitor (to increase superoxide anion synthesis) as well as incubation with N-acetylcysteine, NAC ( an antioxidant).These infection experiments were conducted in 8 well plates in a 5:1 ratio (parasites/cell). Subsequently, we incubated these plates for 4, 24, 48 and 72 hours at 37oC and 5% CO2. After that, the plates were stained and the number of amastigotes (parasite burden) determined. We observed that 14 out 16 isolates treated with menadione showed 50% or more loss of their viability at concentrations varying from 15 to 750 ìM, whereas two of them exhibited even 70% or more viability at 750 mM. From ROS toxicity evaluation for L. L. chagasi amastigotes, we observed in J774.16 cultures infected by ROS susceptible and resistant L. L. chagasi a decrease in parasitic load for both isolates. This decrease in parasite burden was observed also in cultures treated by LMNA, an iNOS inhibitor. Inhibition of SOD by DETC also promoted a decrease in the number of amastigotes for both of these J774.16 cultures from 24 hour infection. The addition of NAC to these cultures increased the number of amastigotes for ROS resistant infected J774.16 cells but nor for those ROS susceptible infected cultures. These data indicate that damage on these amastigotes induced by DETC is oxidative. Thus, it is possible to conclude that reactive oxygen species are crucial toxic agents for L. L. chagasi as in promastigote form, as well as in amastigote form.